Meningkatkan Hasil Belajar Matematika Siswa Kelas VII Menggunakan E-Book Berbasis Pendekatan RME - Aditin Putria; Muhammad Akhyar; Leo Agung Sutimin (Universitas Sebelas Maret, 2017)
This research is an experimental research that aims to test the effectiveness of RME-based e-books in improving mathematics learning outcomes of Grade VII students on the subject of social arithmetic. E-books before being used in experiments have been declared valid and practical based on expert validation and formative revisions. The effectiveness test of an ebook based on RME results in finding that the average value of student learning outcomes tests that use e-books (experimental class) is higher than the average value of student learning outcomes tests that use printed books (control class). Thus, RME-based e-books can be used as a concrete step for solutions to improve students' mathematics learning outcomes in class VII, choosing the RME approach itself is a form of special effort to make students not only have good mathematical values but the significance of mathematics and feel the benefits of mathematics in life daily. E-books and RME are a good combination in facing the era of competition where most jobs require analytical skills rather than merely performing procedural and mechanistic skills.